Discovery Learning, Motivation, and Learning Focus: A Qualitative Study of Vocational Students in the TKR Program - Khanifil Istantina Hasan; Ahmad Faruk (Universitas Islam Negeri Palopo, 2026)
This qualitative case study examines the influence of the Discovery Learning (DL) model on the motivation, learning focus, independence, and self-confidence of tenth-grade students in the Light Vehicle Engineering (TKR) program at SMK NU Sudirman Rogojampi. Data were collected through classroom observations, in-depth interviews with one English teacher and three students, and document analysis, following Miles and Huberman's analytical framework. The findings indicate that DL implementation enhanced student motivation and engagement through active participation in discovery tasks and collaborative discussions. The teacher’s facilitative role was pivotal in guiding students toward autonomous concept discovery, fostering an interactive classroom environment. Additionally, the approach supported the development of student independence and confidence in expressing ideas. This study contributes to the limited qualitative literature on DL within vocational English education, suggesting its potential in promoting a student-centered, practical learning culture aligned with vocational training objectives.